Postharvest application of gum arabic and essential oils for controlling anthracnose and quality of banana and papaya during cold storage. - Maqbool, Mehdi; Ali, Asgar; Alderson, Peter G.; Tengku Muda Mohamed, Mahmud; Siddiqui, Yasmeen; Zahid, Noosheen (Elsevier, 2011)
Management of anthracnose caused by Colletotrichum spp. is the most important issue for the tropical fruit industry because of resulting financial losses. Antifungal effects of gum arabic (GA) (10%), lemongrass oil (LG) (0.05%), cinnamon oil (CM) (0.4%), and their combinations were investigated in vitro and in vivo for controlling postharvest anthracnose of banana and papaya. LG at 0.05% and 0.4% CM showed fungicidal effects against Colletotrichum musae and Colletotrichum gloeosporioides, causal organisms of banana and papaya anthracnose, respectively. GA alone did not show any fungicidal effects while the combination of 0.05% LG and 0.4% CM with Ten percent GA alone showed more fungicidal effects. However, potato dextrose agar (PDA) medium modified with 10% GA combined with 0.4% CM showed the most promising results among all treatments against C. musae and C. gloeosporioides in suppressing the mycelial growth (73.4%) and (70.0%) and spore germination inhibition (88%) and (85%), respectively. In vivo studies also revealed that 10% GA combined with 0.4% CM was the optimal concentration in controlling decay (80%) and (71%), showing a synergistic effect in the reduction of C. musae and C. gloeosporioides, respectively, in artificially inoculated bananas and papayas. The results regarding quality evaluation also confirmed the efficacy of 10% GA combined with 0.4% CM coatings since ripening was significantly delayed, in terms of percentage weight loss, fruit firmness, soluble solids concentration and titratable acidity. The results suggest the possibility of using 10% gum arabic combined with 0.4% cinnamon oil as a biofungicide for controlling postharvest anthracnose in major tropical fruit such as banana and papaya.